Atuação do Ministério Público Federal na fiscalização e acompanhamento da execução do Plano de Desenvolvimento Regional Sustentável do Xingu - NASCIMENTO FILHO, Raimundo Hélio (Universidade Federal do Pará, 2024)
The purpose of this dissertation consists of evaluating the performance of the Federal Public Ministry in supervising and monitoring the execution of the Xingu Sustainable Regional Development Plan, an innovative institution, which emerged from the partnership between the Federal Government and the State Government of Pará, in the context of construction of the Belo Monte HPP, with the purpose of promoting decentralized public policies that result in improving the quality of life of the population living in the territorial area covered by it, the Xingu Integration Region, characterized, among others, due to their multi-level, networked governance. On the other hand, it is known that the Constitution of the Federative Republic of Brazil of 1988 granted important functions to the Public Ministry, a permanent institution, essential to the jurisdiction of the State, whose purpose is to defend the legal order, the democratic regime and social interests. and unavailable individuals (art.127), among others. In line with this constitutional mission, the National Council of the Public Ministry, seeking to sow a culture of institutional results, within the scope of the Brazilian MP, has undertaken its strategic mission of strengthening and promoting responsible and socially effective action, which presupposes the promotion of resolute action, notably in inducing, monitoring and supervising the implementation of public policies that enforce fundamental rights. However, numerous complaints have been received by the Federal Public Ministry about public problems related to the execution of the Xingu PDRS. In effect, these public problems that call for action by the Federal Public Ministry led to the following question: To what extent has the work of the Federal Public Ministry contributed to effectively solving public problems related to the execution of the Xingu PDRS? The study is inclined to confirm, or not, the hypothesis that the actions of the Federal Public Ministry have achieved an unsatisfactory resolution rate for public problems related to the execution of the Xingu PDRS.